K probleme formirovaniya natsionalnoj sportivnoj doktriny (Analiticheskij obzor) - Rybakov, V. V.; Kulikov, L. M. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The basic choice of the strategy of the development of sports culture, the definition of the way on which it will go to the nearest decades and in the remote prospect now is very important. It is necessary to outline its place in the modern society and the civilization of the future and to define those real functions which it can and should carry out. It is possible only at the objective and all-round analysis of laws and tendencies of the social development, the decision of the problem of the choice of the strategy of an human activity.